Cross-priming of minor histocompatibility antigen-specific cytotoxic T cells upon immunization with the heat shock protein gp96 (The Rockefeller University Press, 1995)
Vaccination of mice with heat shock proteins isolated from tumor cells induces immunity to subsequent challenge with those tumor cells the heat shock protein was isolated from but not with other tumor cells (Udono, H., and P.K. Srivastava. 1994. J. Immunol. 152:5398-5403). The specificity of this immune response is caused by tumor-derived peptides bound to the heat shock proteins (Udono., H., and P.K. Srivastava. 1993. J. Exp. Med. 178:1391-1396). Our experiments show that a single immunization with the heat shock protein gp96 isolated from beta- galactosidase (beta-gal) expressing P815 cells (of DBA/2 origin) induces cytotoxic T lymphocytes (CTLs) specific for beta-gal, in addition to minor H antigens expressed by these cells. CTLs can be induced in mice that are major histocompatibility complex (MHC) identical to the gp96 donor cells (H-2d) as well as in mice with a different MHC (H-2b). Thus gp96 is able to induce "cross priming" (Matzinger, P., and M.J. Bevan. 1977. Cell. Immunol. 33:92-100), indicating that gp96-associated peptides are not limited to the MHC class I ligands of the gp96 donor cell. Our data confirm the notion that samples of all cellular antigens presentable by MHC class I molecules are represented by peptides associated with gp96 molecules of that cell, even if the fitting MHC molecule is not expressed. In addition, we extend previous reports on the in vivo immunogenicity of peptides associated gp96 molecules to two new groups of antigens, minor H antigens, and proteins expressed in the cytosol.